Prevenir para preservar. Os desafios da prevenção a incêndios em duas igrejas do Triângulo Mineiro - Cristaldo, Peter Peixoto (2022)
This research proposes studies in the theoretical, practical and methodological fields of fire safety in buildings that are part of the cultural heritage built in the state of Minas Gerais. From a theoretical and critical foundation about the state regulations that deal with the subject, and concomitant with the bibliographic review in the fields of conservation and restoration, an ideal structuring of project parameters is sought that balance, in cultural assets, the demands of prevention and fire safety, allied to the conscious maintenance of its layers of historical and artistic value, considering that the prevention criteria currently supported in the state are applied without taking into account the diversity and specificity of each building and that sometimes such parameters are in conflict with propositions that aim to preserve them as historical documents and architectural objects bearing artistic value. The present work, in addition to approaching the norms and technical instructions that deal with fire prevention in these examples, proposes to investigate in the practical and operational field two objects of study in the Triângulo Mineiro region, similar in typology, but different in scale, historicity, formal evolution. and constructive, which are the churches of Divino Espírito Santo do Cerrado, in Uberlândia/MG, and the Mother Church of Nossa Senhora do Desterro, in the District of Desemboque, in Sacramento/MG, opportune objects of project performance in the face of fire safety in sets architectural projects, whose scope serves as a reference for the construction of the research.